In situ confined-synthesis of mesoporous FeS2@C superparticles and their enhanced sodium-ion storage properties. Issue 9 (4th January 2019) - Yao, Luyin; Wang, Biwei; Yang, Yuchi; Chen, Xiao; Hu, Jianhua; Yang, Dong; Dong, Angang
Abstract : Mesoporous superparticles composed of ultrasmall FeS2 @C nanoparticles have been designed for high-performance Na-ion storage. Abstract : Mesoporous FeS2 @C superparticles chemically converted from Fe3 O4 nanoparticle superlattices were used as anode materials for sodium-ion batteries with superior electrochemical performance. The partial etching of Fe3 O4 nanoparticles creates appropriate void space, which is beneficial for confining the growth of ultrasmall FeS2 nanoparticles during sulfidation and for mitigating volume change of active materials during cycling.